(untitled) (Research, Society and Development, 2024)
This study’s main objective is to analyze the epidemiological profile of cases of Traumatic Brain Injury (TBI) in the state of Tocantins over a decade, covering the period from 2020 to 2021 in the 3 largest cities in the state, Palmas, Gurupi and Araguaína. The research, of a quantitative nature, used data from DATASUS to identify patterns and trends related to age, sex and place of occurrence of cases. The results demonstrated that TBI is a relevant public health problem in the state, with a higher prevalence among men, especially in the 20 to 29 age group. Palmas had the highest number of deaths, followed by Araguaína and Gurupi. Data analysis reveals the need for preventive and health promotion actions, such as educational campaigns on traffic safety and the use of protective equipment, as well as investments in infrastructure and specialized health services. The identification of the most vulnerable groups allows actions to be directed more effectively, contributing to reducing the incidence and severity of TBIs in Tocantins.